RELATIONSHIPS OF PRIMARY AND SECONDARY WHEAT YIELD COMPONENTS - Loro, Murilo Vieira; Carvalho, Ivan Ricardo; Silva, José Antonio Gonzalez da; Moura, Natã Balssan; Hutra, Danieli Jacoboski; Lautenchleger, Francine; Souza, Velci Queiróz de (REVISTA DE AGRICULTURA, 2021)
The aim is to improve production techniques, so the study aims to verify the change in the productivity dynamics of ears contained in the main stems and tillers related to the sowing densities and dual purpose wheat cultivars. The experiment was carried out in Frederico Westphalen, RS. The design used was randomized blocks organized in factorial scheme, with five wheat cultivars, five density managements, arranged in three repetitions. In the analysis of variance, interaction for cultivar and density was observed for all variables analyzed, except for ear length in the main plant, tiller ear length, grain mass per tiller indicating that the interaction between both collaborated to obtain the results. The cultivar BRS Tarumã, BRS Figueira and BRS Guatambu showed to be able to compensate the production in higher densities, increasing the values of some variables analyzed. All yield components show positive correlations.